Punishment: A comparative historical perspective - Hong, Lu (Cambridge University, 2013)
Informed by current scholarship, yet tailored to the needs of undergraduate students, this textbook presents a broad perspective on one of the most fundamental social practices. Punishment is the common response to crime and deviance in all societies. However, its particular form and purpose are also linked to specific structural features of these societies in a particular time and place. Through a comparative historical analysis, the authors identify and examine the sources of similarity and difference in types of economic punishments, incapacitation devices and structures, and lethal and nonlethal forms of corporal punishment over time and place.